2019
DOI: 10.2337/dc18-1126
|View full text |Cite|
|
Sign up to set email alerts
|

Should Viscous Fiber Supplements Be Considered in Diabetes Control? Results From a Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Evidence from randomized controlled trials (RCTs) suggests that viscous dietary fiber may offer beneficial effects on glycemic control and, thus, an improved cardiovascular disease risk profile. Our purpose was to conduct a systematic review and meta-analysis of RCTs to synthesize the therapeutic effect of viscous fiber supplementation on glycemic control in type 2 diabetes. RESEARCH DESIGN AND METHODS MEDLINE, Embase, and Cochrane Central Register of Controlled Trials were searched through 15 June 2018. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 51 publications
3
59
0
5
Order By: Relevance
“…We excluded a number of trials included in the 2013 review, which involved changes in other nutrients in addition to an increase in dietary fibre [77,78], comparisons of one type of fibre with another [79][80][81], or compared a fibre-rich diet with another dietary intervention [82]. Two more recent reviews have been published; one considered the effects of viscous fibre [15], and the other was an umbrella review which provided no new analyses [16].…”
Section: What the Study Adds To The Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…We excluded a number of trials included in the 2013 review, which involved changes in other nutrients in addition to an increase in dietary fibre [77,78], comparisons of one type of fibre with another [79][80][81], or compared a fibre-rich diet with another dietary intervention [82]. Two more recent reviews have been published; one considered the effects of viscous fibre [15], and the other was an umbrella review which provided no new analyses [16].…”
Section: What the Study Adds To The Existing Literaturementioning
confidence: 99%
“…Previous meta-analyses of clinical trials have demonstrated the potential of fibre supplements derived from psyllium [89] or viscous sources [15] to improve glycaemic control and cardiometabolic risk factors. European guidelines for the management of type 1 and type 2 diabetes have emphasised the benefits of soluble forms of dietary fibre from legumes [90].…”
Section: Implications Of Our Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibers have been shown to exhibit different physiological effects and to provide a plethora of positive health outcomes, such as satiation [1,2], and regulation of digestion [3] and cardiovascular disease [4,5], thereby reducing the risk of numerous diet-related diseases such as diabetes mellitus type 2 [6,7]. Regarding glucose metabolism, besides insoluble resistant starch [8] and soluble dietary fibers [9], the consumption of highly purified insoluble dietary fibers from wheat was associated with reducing the post-prandial glucose response [10].…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis paper by Jovanovski et al ( 3 ), which analyzed 28 soluble fiber supplementation RCTs, found that fiber supplementation significantly improved HbA 1c , fasting glucose, fasting insulin, and HOMA of insulin resistance among patients with diabetes. Given the short duration of these trials (median of ∼8 weeks), the longer-term effects of fiber supplementation in diabetes management are still uncertain.…”
mentioning
confidence: 99%